2012
DOI: 10.1159/000336325
|View full text |Cite
|
Sign up to set email alerts
|

Recent Secular Trends in Pubertal Timing: Implications for Evaluation and Diagnosis of Precocious Puberty

Abstract: The decline in age at puberty in the general population has been paralleled by an increase in the number of girls referred for evaluation of precocious puberty (PP). In 1999, The Lawson Wilkins Pediatric Endocrine Society recommended a lowering of the age limit for evaluation of PP in girls. However, the limited evidence on which these recommendations were based led many experts to question these new suggestions. The emergence of new European pubertal timing data evaluated by robust clinical as well as biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
222
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(240 citation statements)
references
References 112 publications
6
222
1
11
Order By: Relevance
“…This difference is could be due to the contribution of ethnic differences because we have noticed that our sample is miscegenated with genetic characteristics that are definitely different from those of the British girls evaluated by those authors. Moreover, our study is much more recent, and it is recognised that there is a phenomenon of secular reduction in the age of onset of the secondary sexual characteristics in several populations, especially in developing countries such as Brazil (4,5).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This difference is could be due to the contribution of ethnic differences because we have noticed that our sample is miscegenated with genetic characteristics that are definitely different from those of the British girls evaluated by those authors. Moreover, our study is much more recent, and it is recognised that there is a phenomenon of secular reduction in the age of onset of the secondary sexual characteristics in several populations, especially in developing countries such as Brazil (4,5).…”
Section: Discussionmentioning
confidence: 81%
“…However, it has been reported that the age and time of progression of puberty have diminished (3,4) worldwide, and studies have indicated a secular reduction in the age of menarche and thelarche (3)(4)(5). Based on these data, the Lawson Wilkins Paediatric Endocrine Society (LWPES) even suggested that it could be considered normal for pubertal evolution to begin at 7 years of age for white girls and 6 years of age for black girls (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of reliable data from European sources, work on the subject has also shown disagreement over the appropriateness of transposing data from the US: some use the data to support their clinical observations (Pienkowski and Granjean, 2008;Cartault et al, 2008); others contest their validity given the differences between the populations under study and the results (even interim) obtained (Gaudineau et al, 2010;Sørensen et al, 2012). …”
Section: Early Puberty: Gender and Age Timing At Stake A Literature mentioning
confidence: 99%
“…These findings reinforce the idea that the prevalence of sexual precocity is underestimated. In fact, parent's education regarding the detection of first pubertal signs is essential for prompt recognition of precocious puberty (8,9).…”
mentioning
confidence: 99%
“…(7), the prevalence of overweight and obesity was 18.8 and 12.5%, respectively. Other studies have documented that higher BMI is correlated with earlier onset of puberty, implicating leptin, a fat cell-derived protein, and other adipokines required for normal gonadotropin secretion (3,6,9). However, it is not clear if increased adiposity is the cause or the consequence of early pubertal development in girls.…”
mentioning
confidence: 99%